IMAM THABARI METHOD IN INTERPRETING ALQUR’AN - Ety Najikhatul Himmah (Jurnal Ilmiah Pesantren, 2019)
ABSTRACT The science of tafsir is one of the important branches of knowledge in Islamic science. Further, in order to revive the Qur’anic verses must be repudiated, understood and then practiced by the Muslim people. So, the purpose of the Qur'an is revealed. Moreover, in term of kind, the tafsir of interpretation is divided into two, namely tafsir bil ma'tsur and tafsir bil ra'yi, tafsir bil ma'tsur is tafsir which based on the hadiths of the prophet about the interpretation of the Qur’anic verses, while tafsir bil ra 'yi is the interpretation of the verses of the Qur'an rests on the opinions of the muslim scholars namely interpreter. And from this classification the scholars created the science of methodology in interpreting Qur'an, which from this science is summed up the ways of the scholars mufassir in interpreting the Qur'an. This branch of knowledge was created to make it as a guideline in interpreting the Qur'an to avoid misguided and perverted interpretations. And through this paper, the author will examine the method of Imam Tabari in interpreting the Qur'an. While, his interpretation is belongs to tafsir bil ma'tsur. Because in his interpretation, most of the verses refer to the hadith of the prophet and atsar shahabah. Tafsir Imam Thabari is the first generation of commentary scholars who became the main reference of the salaf scholars and contemporary mufassir. Furthermore, tahliliy method or method of analysis is the main method used Imam Tabari in his tafsir, which is to interpret the Qur'an by explaining his verses from all aspects contained in detail. Keywords: Tafsir, Method of Interpretation, Imam Thabari